Pengaruh Modal Intelektual Terhadap Kinerja Keuangan Perusahaan Perkebunan Yang Terdaftar di Bursa Efek Indonesia - Simamora, Juan feri; Rifai, Ahmad; Muwardi, Didi (Universitas Galuh, 2025)
ABSTRACT In the future, plantation companies will face land problems due to the increasing limitations of plantation company land resources. Therefore, in order to maintain and increase the value of the company, innovation and development of intangible assets of plantation companies are needed. This study aims to analyze the effect of intellectual capital on the financial performance of plantation companies. The sample used in this study was 36 companies listed on the Indonesia Stock Exchange. The data used in this study are the financial reports of 10 listed companies listed on the Indonesia Stock Exchange for the period 2021-2023. This study uses panel data regression analysis to analyze the effect of the variables Value Added Capital Employed (VACA), Value Added Human Capital (VAHU), and Structural Capital Value Added (STVA), on financial performance, namely Return on Assets (ROA) and Return on Equity (ROE). The results of the study show that intellectual capital has an effect on financial performance, both ROA and ROE. Partially, VACA and VAHU have a significant and positive effect on ROA, while VACA and STVA have a significant and positive effect on ROE.